English-language videos on YouTube as a source of information HPV vaccination - Onder Dirican, Aylin; Topfedaisi Ozkan, Nazli; Bektas, Gizem (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the quality of information presented in YouTube videos about human papillomavirus vaccination. Method: The descriptive study was conducted at Konya Meram Education and Research Hospital, On October 15, 2019 when the YouTube website was search using the terms ‘human papillomavirus’, ‘HPV vaccine’ and ‘Gardasil’. The videos were recorded to a playlist by two individual gynaecologists to prevent any change in the listed videos. The videos were categorised into 3 groups; useful information group A, misleading information group B and insufficient information group C. The quality of the videos was scored using global quality scale from 1 = poor quality to 5 = excellent quality. DISCERN scale was used for reliability. A 10-point scale was used to evaluate comprehensiveness of the videos. Data was analysed using SPSS 20. Results: Of the 200 videos assessed, 179(89.5%) were analysed. There were 17(9.5%) videos in group A, 38(21.2%) in group B and 124(69.3%) in group C. Mean global quality scale score was 3.94±1.39 group A, 1.84±0.59 group B and 3.13±0.94 group C (p<0.001). Mean reliability values were 4.18±1.13group A, 1.66±0.66 group B and 3.03±0.87 group C (p<0.001). Comprehensiveness scores were 6.94±2.49 group A, 1.53±0.95 group B and 4.87±1.72 group C (p<0.001). Conclusion: Professional organisations, university channels and doctors should provide accurate, unbiased and evidence-based information on YouTube for community awareness. Key Words: HPV vaccine, Health information on YouTube, e-health, Health communication.